The additive impact of cardio‐metabolic disorders and psychiatric illnesses on accelerated brain aging. Issue 6 (3rd February 2022) - Ryan, Meghann C.; Hong, L. Elliot; Hatch, Kathryn S.; Gao, Si; Chen, Shuo; Haerian, Krystl; Wang, Jingtao; Goldwaser, Eric L.; Du, Xiaoming; Adhikari, Bhim M.; Bruce, Heather; Hare, Stephanie; et al.
Abstract: Severe mental illnesses (SMI) including major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia spectrum disorder (SSD) elevate accelerated brain aging risks. Cardio‐metabolic disorders (CMD) are common comorbidities in SMI and negatively impact brain health. We validated a linear quantile regression index (QRI) approach against the machine learning "BrainAge" index in an independent SSD cohort ( N = 206). We tested the direct and additive effects of SMI and CMD effects on accelerated brain aging in the N = 1, 618 (604 M/1, 014 F, average age = 63.53 ± 7.38) subjects with SMI and N = 11, 849 (5, 719 M/6, 130 F; 64.42 ± 7.38) controls from the UK Biobank. Subjects were subdivided based on diagnostic status: SMI+/CMD+ ( N = 665), SMI+/CMD− ( N = 964), SMI−/CMD+ ( N = 3, 765), SMI−/CMD− ( N = 8, 083). SMI ( F = 40.47, p = 2.06 × 10 −10 ) and CMD ( F = 24.69, p = 6.82 × 10 −7 ) significantly, independently impacted whole‐brain QRI in SMI+. SSD had the largest effect (Cohen's d = 1.42) then BD ( d = 0.55), and MDD ( d = 0.15). Hypertension had a significant effect on SMI+ ( d = 0.19) and SMI− ( d = 0.14). SMI effects were direct, independent of MD, and remained significant after correcting for effects of antipsychotic medications. Whole‐brain QRI was significantly ( p < 10 −16 ) associated with the volume of white matter hyperintensities (WMH). However, WMH did not show significant association with SMI and was driven by CMD, chiefly hypertension ( p < 10 −16 ). We used a simple and robust index, QRI, the demonstrate additive effect of SMI and CMD on accelerated brain aging. We showed a greater effect of psychiatric illnesses on QRI compared to cardio‐metabolic illness. Our findings suggest that subjects with SMI should be among the targets for interventions to protect against age‐related cognitive decline. Abstract : Severe mental illnesses including major depressive disorder, bipolar disorder, and schizophrenia spectrum disorder elevate accelerated brain aging risks; cardio‐metabolic disorders are common comorbidities and can negatively impact brain health. We used a simple and robust index, QRI, the demonstrate additive effect of SMI and CMD on accelerated brain aging. We showed a greater effect of psychiatric illnesses on QRI compared to cardio‐metabolic illness.